2022
DOI: 10.26773/jaspe.220104
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Physical Activity, Physical Fitness and Well-being of Students During The Lock-Down Due to Covid-19 Pandemic

Abstract: Restricting movement for the population and the impact of preventative measures due to the COVID-19 pandemic have spurred research interests in analyzing the healthy lifestyle of the student population. The aim of the study was to examine gender differences between students in physical activity, and the perceptions of physical fitness and well-being during lock-down due to COVID-19. The sample consisted of male (n=268; 25.9%; age 22.56±2.12) and female students (n=768; 74.1%; age 22.12±1.73) at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…During the pandemic, a lot of people (men in particular), despite quarantine and restrictions, began to take up various forms of PA in order to strengthen their immune system, improve their mental health and reduce negative psychological effects of the pandemic ( 59 ). Bajramovic et al ( 60 ) showed that women manifested lower levels of PA compared to men, which is consistent with our findings. However, the reported PA had a positive effect on students’ well-being both among women and men ( 60 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During the pandemic, a lot of people (men in particular), despite quarantine and restrictions, began to take up various forms of PA in order to strengthen their immune system, improve their mental health and reduce negative psychological effects of the pandemic ( 59 ). Bajramovic et al ( 60 ) showed that women manifested lower levels of PA compared to men, which is consistent with our findings. However, the reported PA had a positive effect on students’ well-being both among women and men ( 60 ).…”
Section: Discussionsupporting
confidence: 93%
“…Bajramovic et al ( 60 ) showed that women manifested lower levels of PA compared to men, which is consistent with our findings. However, the reported PA had a positive effect on students’ well-being both among women and men ( 60 ). Despite pandemic-related restrictions, the vast majority of students from Poland and Belarus met WHO’s recommendations regarding PA ( 1 ) Rousset et al ( 61 ) drew similar conclusions with regard to young adult students from France.…”
Section: Discussionsupporting
confidence: 93%
“…Insufficient physical activity is a serious health concern among university students. The average level of physical activity in men and women was significantly reduced during the COVID-19 pandemic [5] . A direct consequence of a sedentary lifestyle and excessive time spent using technology.…”
Section: Introductionmentioning
confidence: 95%